If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(-4)+8-2m=3(m+4)
We move all terms to the left:
4(-4)+8-2m-(3(m+4))=0
We add all the numbers together, and all the variables
-2m-(3(m+4))-8=0
We calculate terms in parentheses: -(3(m+4)), so:We get rid of parentheses
3(m+4)
We multiply parentheses
3m+12
Back to the equation:
-(3m+12)
-2m-3m-12-8=0
We add all the numbers together, and all the variables
-5m-20=0
We move all terms containing m to the left, all other terms to the right
-5m=20
m=20/-5
m=-4
| 6w+3=-6w+15 | | 0.2(r+0.5)+5.24=1.5r+0.7(r+2.2) | | 9x-3x-12(3)=5x+24X= | | 4(4)+8-2m=3(m+4) | | 0.2x+0.6=3.0 | | 3x-8=-14* | | | | 0.3x-1.5=4.5 | | 7q-5=12q+30* | | 3x2−5x−8=0 | | 3(x-2.4=4x+4 | | 6s+3=57 | | 6d+18=30 | | 6(-6-5v)=86 | | m-32=-66 | | 7m-9=4 | | 8=y÷14 | | 1/5(r+0.5)+5.24=3/2r+7/10(r+2.2) | | 9y-5=15y-17* | | 69d+15=429 | | 15=x÷2 | | 8=14y | | 5c-6=2c+15 | | 4(5z-7)=88 | | 3(2x+4)=5(x+4) | | 14=8y | | 4x-2x+6=10x-2 | | 3z/10-5=-6 | | 2w+2(2w+3)=804 | | 6t+2=32 | | -9r=-7r+8 | | 16-4m=m |